Rehabilitation with Cochlear Implant in Patient with Harboyan Syndrome - Paniagua,Lauren Medeiros (2013)
Background  Harboyan syndrome, defined as congenital corneal dystrophy associated with progressive sensorineural hearing loss, was first described by Harboyan in 1971. It is a hereditary disease manifested by eye lesions consistent with corneal endothelial dystrophy and progressive sensorineural hearing loss. There is bilateral symmetric progressive hearing loss, which may be either dominant or recessive. Objective  To report a case of a patient with a diagnosis of Harboyan syndrome. Case Report  A 25-year-old woman with profound bilateral sensorineural hearing loss, showing poor hearing performance while using a personal sound amplification device, underwent hearing rehabilitation with a cochlear implant. Conclusion  Rehabilitation was imperative in this case. The cochlear implant has proven to be the best therapeutic option, providing the patient with a better quality of life.